PENGARUH MODEL PEMBELAJARAN INQUIRY TERHADAP TEKNIK DASAR LAY UP PESERTA DIDIK DI SMA - Atmaja, Romadani Kusuma; Simanjuntak, Victor G.; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe method used is an experimental method to study the form of true experimental design. The population in this study is a class XI were 9 classes. The samples in this study using purposive sampling technique, totaling 33 people as classroom control while totaling 33 people as a class experiment. Data was analyzed using computerized systems as well as analysis by using t-test.Based on t-test results on the class dick and experimental value 0,000 p value <0.05 then Ho is rejected (Ha acceptable) means that there is a significant improvement between the before and after treatment, in which the mean value of the difference in the experimental class (17.9) greater than the control group (8.8).Keywords: Inquiry, Basic Techniques, Lay Up.Â